1975
DOI: 10.1073/pnas.72.1.240
|View full text |Cite
|
Sign up to set email alerts
|

An electrophoretic variant of beta-galactosidase with altered catalytic properties in a patient with GM1 gangliosidosis.

Abstract: In nine patients with GM, gangliosidosis, liver ganglioside GM1 B-galactosidase (EC 3.2.1.23) activity ranged from less than 0.01% to 0.05% of normal. In a tenth patient's liver, much higher activity was found (0.5% of normal). In this patient the residual enzyme had the same molecular weight as fl-galactosidase A, the major form of 6-galactosidase of normal human liver. No activity was found that corresponded to j3-galactosidase B, the minor form of human liver #-galactosidase. On starch gel electrophoresis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

1975
1975
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Dr. Norden and I (Norden & O'Brien 1975) studied in detail one unusual patient (CE) with a phenotype similar to Type 2.…”
Section: Nature Of the Mutation In G M Cangliosidosismentioning
confidence: 99%
“…Dr. Norden and I (Norden & O'Brien 1975) studied in detail one unusual patient (CE) with a phenotype similar to Type 2.…”
Section: Nature Of the Mutation In G M Cangliosidosismentioning
confidence: 99%
“…These fi ndings suggested that cholesterol was a secondary storage molecule to GM1 in this disease. GM1 gangliosidosis is an autosomal recessive glycosphingolipid storage disorder caused by mutations in lysosomal ␤ -galactosidase activity (18)(19)(20). The loss or reduction of ␤ -galactosidase activity results in a failure to cleave the terminal galactosyl residue of ganglioside GM1, leading to excessive central nervous system storage of GM1 and its asialo derivative, GA1 (21)(22)(23)(24)(25).…”
mentioning
confidence: 99%
“…A molecular abnormality of 13-galactosidase was reported in a case of GMt-gangliosidosis with an abnormal electrophoretic mobility of the residual enzyme activity (Norden and O'Brien, 1975). However, no other direct evidence has been presented with respect to the structure of the inactive enzyme molecules in this disease.…”
Section: Discussion-and Conclusionmentioning
confidence: 97%